Chitosan ameliorates growth and biochemical attributes in mungbean varieties under saline condition - Ray, Shuma Rani; Bhuiyan, Muhammad Javidul Haque; Hossain, Mohammad Anowar; Hasan, Ahmed Khairul; Sharmin, Shayla (Research in Agriculture Livestock and Fisheries, 2016)
The pot experiment was conducted to evaluate the effect of chitosan on the morphological, biochemical parameters of four Mungbean varieties (BARI Mung3, BARI Mung6, BINA Mung5 and BINA Mung8) under salinity condition. Each pot having eight kilograms of soil was prepared to grow three plants of each variety. The experiment comprised with four different conditions in triplicates viz. control, saline (40 mM NaCl, 25 days after sowing- DAS), saline plus chitosan (25 ppm chitosan, 30DAS on saline condition) and chitosan (25 ppm chitosan on control condition). Seed collections followed by data analysis were done. Proline content was measured accordingly. Salinity caused reduction in all growth and yield contributing attributes compared to control groups of all four varieties. Proline accumulation was enhanced due to saline condition, and this accumulation was not enhanced by application of chitosan. However, application of chitosan played as an outstanding stimulating role in all morphological parameters like number of flowers plant-1, number of pods plant-1, number of seeds pod-1 and thousand seeds weight under salinity stress. Res. Agric., Livest. Fish.3(1): 45-51, April 2016